Damage microstructure evolution of helium ion irradiated SiC under fusion relevant temperatures. Issue 11 (September 2018) - Harrison, R.W.; Ebert, S.; Hinks, J.A.; Donnelly, S.E.
Abstract: In-situ transmission electron microscopy (TEM) with ion irradiation has been used to study the damage microstructure evolution of He ion irradiated 4-H SiC at nuclear fusion relevant temperatures. The SiC samples were irradiated with 20 keV He ions at 25, 400, 800 and 1200 °C to a dose of 5.0 displacements per atom (DPA). At 25 °C, the material fully amorphises at 1.5 DPA and no He bubble nucleation occurs up to the doses studied. At 400 and 800 °C, He bubble nucleation occurs and the material remains crystalline. Bubble nucleation occurs at 2.0 DPA at 400 °C but occurs at only 0.5 DPA at 1200 °C. This is attributed the He atoms de-trapping from vacancies and migrating interstitially to larger He-vacancy clusters at higher temperatures, leading to faster nucleation of observable He bubbles. Helium platelets form at an irradiation temperature of 1200 °C at 0.5 DPA showing a preference for nucleation between the 0001 basal planes.